The Role of AI and Informal Digital Learning in Strengthening Secondary Islamic teacher training in Southern Pakistan - kashif Majeed,; Dr.Tunku Badariah Ahmad, (MEI, 2025)
This paper dwells on how Artificial Intelligence (AI) and informal digital learning may be implemented to improve the training of teachers at the secondary Islamic schools in the region of Karachi in Southern Pakistan, where the process of digital transformation remains at its initial stages. It is aimed at getting familiar with the knowledge of teachers and gender-related disparities in digital skills to assist in designing educationally inclusive training programs regarding current educational demands. Although the concept of AI and digital learning has been researched broadly in the field of general education, little has been discussed about its use in Islamic teacher training education, especially at the secondary level and in relations to gender-based approach. The study was evaluated the knowledge of secondary Islamic teachers regarding the AI and digital informal and the district of Kot Addu in Southern Pakistan. It also aims at examining the connection between the two factors as well as how they influence teacher training. The other objective is to compare knowledge and application difference on basis of gender and to identify higher and lower levels ones in Tehsils. There was an adoption of a quantitative research design. A total of the four Tehsils of District Kot Addu by name Kot Addu, Chowk Sarwar Shaheed, Dera Din Panah, and Mehmood Kot all the secondary Islamic school teachers came as the population. Stratified random selection of 450 teachers was done. Data were gathered based on a structured questionnaire and statistical tools utilized in analysis. The outcomes disclosed the disparities in AI and digital informal learning knowledge in terms of tehsil and gender differences. There was a high degree of correlation between the two variables. To enhance the digital skills of the Islamic teacher education, the findings give strong incentives to develop gender-sensitive training interventions.